Análisis de la relación entre el gasto público y el crecimiento económico en la región Loreto durante el periodo 2013-2023 - Cornejo Rodriguez, Ariana (2025)
An analysis of the relationship between public spending and economic growth in Loreto shows a moderate correlation of 0.3928, indicating a positive but not very strong relationship between the two variables. The significance test P > 0.2321 suggests that approximately 23.21% of the variability in economic growth can be explained by public spending, implying that other factors also influence the region's economic development. The normality test, which resulted in 0.87958 for public spending and 0.96849 for economic growth, assesses whether the data follow a normal distribution. The Prob > z values of 0.10278 and 0.87090, respectively, indicate insufficient evidence to reject the null hypothesis of normality, suggesting that the variables may follow a normal distribution. The z-statistic for public spending is 1.266 and for economic growth is -1.131, which reinforces the interpretation that the data do not present significant deviations from normality. In conclusion, although public spending has a positive relationship with economic growth in Loreto, its impact is limited.